Educational Needs Assessment for General Practitioners in the Field of Neurological Diseases in the Regulatory Zone of Rafsanjan University of Medical Sciences Iran - Alireza Vakilian; Farhad Iranmanesh; Mohammad Ali Shafa; Amir Moghadam-Ahmadi; Fariba Maleki-Rad (Kerman University of Medical Sciences, 2015)
Background & Objective: Regarding the significance of neurological diseases training general practitioners has a key role and they should be welltrained in diagnose and approaching different diseases in this field We focused on educational needs assessment for general practitioners in the field of neurological diseases Methods: All the general practitioners practicing in the regulatory zone of Rafsanjan University of Medical Sciences Iran (urban and rural areas) who agreed to participate were entered the study 104 participants of the total of 170 general practitioners in this area completed a researchermade questionnaire and mailed us The questionnaire encompassed 54 neurological diseases four paraclinical tests and 9 approaches for neurological signs and symptoms as well as their practical framework satisfaction from their education and demographic and educational items Results: In 479% of cases educational expectations were at the level of screening and refer in that 314% at the level of diagnosis and treatment and in 188% at the level of acquaintance and describing The remainders (188%) were the cases with no need to know and unfamiliar ones Statistically screening and refer just the diagnosis and the treatment were the mentioned educational expectations respectively Most of general practitioners were not fully satisfied from their externship and internship educational programs Conclusion: This study in a more systematic way outlines the general practitioners points of view and their tendency to intervene in the procedure of neurological managements which can also be of great use to any further modifications in medical training curricula Absence of perfect satisfaction about educational programs shows us that we should change our educational methods to more practical and clinical forms